Organization of joint business of Azerbaijan with Russia - Tarbiz Nasib Aliyev (Informaciâ i Innovacii, 2018)
Relevance. Joint economic structures occupy an important place in the economy of Azerbaijan. They are actively involved in the formation of GDP and the organization of new highly paid jobs. However, the prevailing number of these enterprises are small ones, and the volume of their production tends to decrease. The number of them representing the CIS countries is insignificant and they are not sufficiently developed on the territory of the Republic. Up to 20% are foreign and joint ventures out of the total number of annually liquidated business structures. All these facts urgently require the development and implementation of scientifically based recommendations for improving the activities of joint ventures in the Republic. Goal. Assess the state of the organization of joint business in Azerbaijan, identify relevant reserves and propose specific recommendations for their rational use. Methods. The methods of the economic-statistical grouping, the graphic method of comparative analysis were used in the article. Results. The factors negatively influencing the effective organization of joint business are revealed. Conclusions. As a result of the analysis, it was revealed that the irrational placement of foreign and joint ventures in the spheres of economic activity and regions adversely affects the growth of production volume and the development of innovative infrastructures. For the rational organization of joint business, it is necessary to develop real investment projects, to increase diversification in the sectoral structure, to intensify the process of creating joint ventures in the agricultural sector and in the manufacturing sub-sectors.